The effects of marketing mix on the customer satisfaction of Ar-rahnu by Agrobank Alor Gajah, Melaka / Mohd Alif Nurfahmi Saad - Saad, Mohd Alif Nurfahmi (Faculty of Business and Management, 2011)
This study is focus on customer satisfaction and marketing mix which is product, place, price and promotion toward Ar Rahnu by Agrobank Alor Gajah, Melaka. Apart from that, this study conducted focusing on “The Effects of Marketing Mix on the Customer Satisfaction of Ar Rahnu by Agrobank Alor Gajah, Melaka. The main objectives of this study are to find out level of the customer satisfaction of the Ar Rahnu offered by Agrobank Alor Gajah, Melaka, to analyze the associations between marketing mix and customer satisfaction toward Ar Rahnu by Argobank Alor Gajah, Melaka and to find out the element of marketing mix contributing the most in customer satisfaction by Ar Rahnu Alor Gajah, Melaka. The study was conducted at Agrobank located at Alor Gajah, Melaka and researcher had distributed the questionnaires to the Ar Rahnu’s customers and 100 respondents selected in order to obtain the findings regarding the topic. The researcher used the descriptive study in order to explore the problem regards the topics. In this research, the study consists of four variables of marketing mix as independent variables and customer satisfaction as a dependent variable toward Ar Rahnu at Argobank Alor Gajah, Melaka. The primary and secondary data has been use for this study to collect the sources. The data obtained from the questionnaires are being analyzed by using SPSS 17.0.